ANALISIS KERUSAKAN JALAN MENGGUNAKAN PROGRAM KENPAVE TERHADAP TEBAL PERKERASAN YANG DIDESIGN MENGGUNAKAN METODE ANALISA KOMPONEN, AUSTROAD DAN ASPHALT INSTITUTE - Rahmawati, Anita; Setiawan, Dian; Pangestu, Mohammad Aby Yansun; Aulia, Robith Azkal (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2018)
In order to improve and develop road quality, it is necessary to evaluate pavement thickness using the Analisa Komponen Method, the Austroads Method and the Asphalt Institute Method, then analyze pavement damage using Kenpave Program to know strain value that happened on road due to traffic load. Based on calculations that have been done, the results of pavement thickness of Analisa Komponen Method, that are the surface layer of 7,5 cm (Laston MS 340), the base layer of 10 cm (Laston Atas MS 340) and the subbase layer of 15 cm (Sirtu Class B). Austroads Method, that are the surface layer of 7,5 cm (Laston MS 340), the base layer of 13 cm (Laston Atas MS 340) and the subbase layer of 50 cm (Sirtu Class B). While for Asphalt Institute Method, that are the surface layer of 5 cm (Laston MS 340), the base layer of 10 cm (Laston Up MS 340) and the subbase layer of 15 cm (Sirtu Class B). Based on the analysis of the damage that has been done, only the Austroads Method is able to reach the life service, while the Analisa Komponen and the Asphalt Institute will experience damage before the life service.